آثر استخدام استراتيجية التعلم التعاوني في التحصيل الدراسي لدى طلاب الصف الثالث الأساسي في مادة التربية الإسلامية - خابور، رشا سامى إسماعيل; بني خلف، ميساء محمد سالم (جامعة محمد الصديق بن يحيى جيجل, 2019)
The study aimed to identify the effect of the use of cooperative learning strategy on the achievement of students in the Third Grade in the Islamic education, and to identify the differences according to the variables of gender, and achievement. To achieve the aim of the study, the researchers prepared a valid and stable questionnaire that included (25) items. It was randomly Class distributed on the sample of the study which consisted of (81) students in the public schools in Irbid Governorate in Jordan. The results of the study showed statistical significant differences among the means due to the specialization. The specializations were ranked with high degrees such as learning process, class activities and educational materials respectively. The study also showed no statistical significance differences due to the gender while there were significant differences due to the achievement of students in favor of good and very good. The two researchers recommended to encourage the students of different achievements to cooperate together, and to innovate new methods of teaching to raise the achievement level of the students.
هدفت الدراسة التعرف إلى أثر استخدام استراتيجية التعلم التعاوني في التحصيل الدراسي لدى طلاب الصف الثالث الأساسي في مادة التربية الإسلامية، والتعرف إلى الفروق تبعا لمتغيرات الجنس، والتقدير، ولتحقيق هدف الدارسة أعدتا الباحثتان استبانة اشتملت على (25) فقرة، وجرى التحقق من صدقها وثباتها. ووزعت بالطريقة الطبقية العشوائية على عينة الدراسة مكونة من (81) طالبا وطالبة في المدارس الحكومية بــــ محافظة إربد في الأردن. وأظهرت نتائج الدراسة أن درجة المتوسطات الحسابية الكلية عن مجالات الدراسة جاءت مرتفعة، أما المجالات فقد جاء مجال العملية التعليمية بالمرتبة الأولى بدرجة عالية، وجاء مجال الأنشطة الصفية بالمرتبة الثانية وبدرجة عالية، وجاء مجال المواد التعليمية بالمرتبة الثالثة، وبدرجة عالية، وأظهرت الدراسة إلى عدم وجود فروق ذات دلالة إحصائية يعزى للجنس في حين يوجد فروق تعزى لتقدير الطلبة لصالح تقدير الجيد والجيد جدا. وأوصت الباحثتان بتشجيع الطلبة بمختلف تقديراتهم لتعاون معا، واستحداث وابتكار طرائق جديدة للتدريس بهدف رفع مستوى التحصيل لدى الطلبة.
Keywords: التربية الإسلامية -- التعلم التعاوني -- التحصيل الدراسي -- طلبة المرحلة الابتدائية -- طرق التدريس